Preventing Revictimization in Teen Dating Relationships, 2010-2013, Denver, Colorado - DePrince, Anne P. ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study addressed the urgent need to target interventions to high risk groups, such as teen girls who have come to the attention of the child welfare system; rigorously test interventions grounded in empirical research on revictimization; and examine processes implied by revictimization theories. In particular, adolescent girls recruited from the child welfare system were randomized to one of two revictimization prevention conditions: social learning/feminist and risk detection/executive function. The study contains one data file with 180 cases and 545 variables.